Leptospira infection of rodents captured at the slaughterhouses and their risk to public health in Unguja island, Tanzania (Journal of Ideas in Health, 2024)
Background: Leptospira infection is an invasion of animal or human body with the pathogenic spirochete bacteria of the genus Leptospira resulting to a disease called leptospirosis. This study aimed to investigate Leptospira infection and the carrier status of rodents caught near slaughterhouses at Unguja Island, Tanzania.Methods: This cross-sectional study was conducted from January to April 2022 at Unguja Island to determine the seroprevalence of Leptospira infection in rodents captured in and around the slaughterhouse’s compounds. A total of 302 sera samples from four slaughterhouses were tested for anti-leptospiral antibodies using microscopic agglutination test (MAT) with a panel of 5 Leptospira serovars: Pomona, Lora, Hebdomadis, Grippotyphosa and Sokoine; and were considered positive at MAT titer ≥1:20. Chi-square test and the Fisher exact test were used to assess the statistical association between variables at a p value of < 0.05.Results: The overall seroprevalence of Leptospira infection in rodents was 10.6% (32/302). Individual rodent species had seroprevalence of 8.5% for Mus musculus, 0.0% for Mastomys natalensis, 20.8% for Rattus norvegicus, 9.3% for Rattus rattus and Cricetomys gambianus at 12.5%. However, the apparent seroprevalence in the individual slaughter facilities was 15.0% (15/100) Kinyasini, 10.4% (5/48) Mfenesini, 9.3% (5/54) Kisakasaka, and 7.0% (7/100) Muwanda.Conclusion: With over ten percent of rodents testing positive for Leptospira infection, it is crucial to implement rodent control measures to prevent the spread of the disease to those working in or around the slaughterhouses in Unguja Island.
Keywords: Rodents, Leptospira infection, Microscopic Agglutination Test, Seroprevalence, slaughterhouses, Unguja Island, Tanzania